Mineração e industrialização de ferro e impactos ambientais - Costa, Ricardo Dalla (2006)
The present work deals with the environmental problem caused by iron ore extraction and industrialization in Brazil. The research starts from international business in three different situations: the free trade which leads to environmental degradation, the protection of the domestic market which also leads to environmental degradation and an intermediate situation between them. Thus, the historical context of the mining sector is analyzed through the public policies, mainly during the government of Getulio Vargas and the foundation of Companhia Siderúrgica Nacional (CSN). Studies of the environmental impact of this field are regulated by law through the EIA/RIMA reports, and are published for public acquaintance and consulting before the mineral exploration. Nevertheless, since the 80s, Companhia Vale do Rio Doce (CVRD) includes a great national power in iron ore exploration, as the Program "Grande Carajás". Its growth barely takes into account the big environmental destruction and much is considered about its responsibility towards society and ecology. In case in CVRD, a pollution enterprise, barriers environmental have carried a bigger preoccupation, and thus, have minimum just impact visible.